2020
DOI: 10.1089/cbr.2019.3021
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DDX11-AS1 Promotes Bladder Cancer Occurrence Via Protecting LAMB3 from Downregulation by Sponging miR-2355-5p

Abstract: Background: As a subtype of human genitourinary system cancer, the morbidity of bladder cancer (BC) continues to rise. Because of the high potentiality of cell metastasis, the 5-year survival rate of BC is relatively low. Long noncoding RNAs (lncRNAs) have been verified by a large body of literature to engage in the tumorigenesis of a few cancers. DDX11-AS1 has been elucidated as a malignancy promoter in several cancers; therefore, its mysterious role in BC attracted our interest as being well worth investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The target gene of SNHG11 was predicted and it was determined that miR-2355-5p was a putative target gene of SNHG11. Previous studies have verified that miR-2355-5p has a suppressive effect in various cancers, including chondrosarcoma ( 23 ) and bladder cancer ( 24 ). In our present study, it was determined that miR-2355-5p expression was downregulated in TNBC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The target gene of SNHG11 was predicted and it was determined that miR-2355-5p was a putative target gene of SNHG11. Previous studies have verified that miR-2355-5p has a suppressive effect in various cancers, including chondrosarcoma ( 23 ) and bladder cancer ( 24 ). In our present study, it was determined that miR-2355-5p expression was downregulated in TNBC.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, microRNA 2355-5p (miR-2355-5p) has received a lot of attention in some cancers. As reported, miR-2355-5p has been revealed to play a role in the suppression of cancer development in a variety of cancers, including chondrosarcoma ( 23 ) and bladder cancer ( 24 ). However, the interaction between SNHG11 and miR-2355-5p in TNBC has not been elucidated and requires further investigation.…”
Section: Introductionmentioning
confidence: 83%
“…Recent studies have demonstrated that DDX11-AS1, as a novel lncRNA, played an imperative function in the progression and metastasis in multiple cancers, including glioma [ 47 ], bladder cancer [ 21 , 22 ], gastric cancer [ 17 , 18 ], hepatocellular carcinoma [ 15 ], and so on [ 14 , 19 , 20 , 23 ]. In the current research, the DDX11-AS1 functions, as well as molecular mechanisms in EMT process of ESCC, were further explored.…”
Section: Resultsmentioning
confidence: 99%
“…The newly discovered lncRNA DDX11-AS1 has been reported to be abnormally highly expressed in a number of malignant tumors, such as liver cancer ( 26 ), colorectal cancer ( 13 ) and bladder cancer ( 27 ). These findings suggested that DDX11-AS1 may be a tumor marker or therapeutic target.…”
Section: Discussionmentioning
confidence: 99%